2015
DOI: 10.1212/wnl.0000000000002121
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and brain structure in a multiethnic elderly cohort

Abstract: Among older adults, MeDi adherence was associated with less brain atrophy, with an effect similar to 5 years of aging. Higher fish and lower meat intake might be the 2 key food elements that contribute to the benefits of MeDi on brain structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
150
7
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(174 citation statements)
references
References 41 publications
14
150
7
3
Order By: Relevance
“…In the small subsample of individuals with dietary habits suggesting a sustained trait of iodine consumption, low animal fat intake and, in general, a low calorie-and-salt diet were associated with preserved lateral brain ventricular size, indicative of reduced or absent brain atrophy. This result is confirmatory of those from a study on 674 non-demented older adults from a multi-ethnic cohort in Manhattan, which concluded that higher fish (iodine-rich, but also a source of other nutrients) and lower meat (energy and protein-rich) intake were the key two elements contributing to the association of the Mediterranean diet with less brain atrophy (22). It also confirms results from another study on 52 individuals cognitively normal but at risk for Alzheimer's disease (AD), which also assessed brain atrophy from brain MRI and found that the nutrient combination identified as "AD-protective" (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…In the small subsample of individuals with dietary habits suggesting a sustained trait of iodine consumption, low animal fat intake and, in general, a low calorie-and-salt diet were associated with preserved lateral brain ventricular size, indicative of reduced or absent brain atrophy. This result is confirmatory of those from a study on 674 non-demented older adults from a multi-ethnic cohort in Manhattan, which concluded that higher fish (iodine-rich, but also a source of other nutrients) and lower meat (energy and protein-rich) intake were the key two elements contributing to the association of the Mediterranean diet with less brain atrophy (22). It also confirms results from another study on 52 individuals cognitively normal but at risk for Alzheimer's disease (AD), which also assessed brain atrophy from brain MRI and found that the nutrient combination identified as "AD-protective" (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…We used multivariate analysis of variance (MANOVA) to see whether the linear combination of the 12 cortical and subcortical regional volumes (see supplementary data)(63) was associated with inflammatory biomarkers. We then examined univariate F tests for individual ROIs.…”
Section: Methodsmentioning
confidence: 99%
“…We then examined univariate F tests for individual ROIs. A similar analysis was conducted for 12 thickness ROIs that have been shown to reflect AD-associated neurodegeneration (63, 64) (see supplementary data), and for 26 white matter tracts (61). Because individual ROI analyses were guided by the MANOVA results, and were essentially exploratory, no correction for multiple comparisons has been performed.…”
Section: Methodsmentioning
confidence: 99%
“…The few published studies on diet and imaging biomarkers suggest that higher adherence to a MeDi dietary pattern is associated with a reduced odds ratio for infarctions [15], larger cortical thickness, and larger brain volumes [16, 17]. However, further studies are needed to better understand the associations of the MeDi pattern and components of the MeDi with MRI biomarkers for specific brain regions that are involved in ageing or AD-related neurodegeneration and atrophy.…”
Section: Introductionmentioning
confidence: 99%